The relationship between the “a” wave depths of the pulmonary valve echocardiogram and the hemodynamic values of patients with isolated valvular pulmonary stenosis - Özkutlu, Süheyla; Saraçlar, Muhsin (The Turkish Journal of Pediatrics, 1987)
This study was carried out on 66 children with pure pulmonary stenosis. Fifty-four healthy children comprised the control group. Hemodynamic and echocardiographic studies were performed on the patients.The relationship between the hemodynamic findings and the “a” wave depths determined by the pulmonary echocardiograms was investigated in all the patients, and the “a” wave depths were measured in all the control subjects.A significant relationship between the ratio of right to left ventricular systolic pressure and the echocardiographic pulmonary “a” wave depth was demonstrated. This finding was more significant when the “a” wave depth was adjusted in accordance with the patient’s body surface or length.
Keywords: echocardiography; pulmonary stenosis; “a” wave depth